Smart cities : issues and challenges : mapping political, social and economic risks and threats - Visvizi, Anna, 1976-; Lytras, Miltiadis D., 1973- (Elsevier, 2019)
Smart Cities: Issues and Challenges: Mapping Political, Social and Economic Risks and Threats serves as a primer on smart cities, providing readers with no prior knowledge on smart cities with an understanding of the current smart cities debates. Gathering cutting-edge research and insights from academics, practitioners and policymakers around the globe, it identifies and discusses the nascent threats and challenges contemporary urban areas face, highlighting the drivers and ways of navigating these issues in an effective manner. Uniquely providing a blend of conceptual academic analysis with empirical insights, the book produces policy recommendations that boost urban sustainability and resilience.